2008
DOI: 10.1111/j.1349-7006.2008.00894.x
|View full text |Cite
|
Sign up to set email alerts
|

High mobility group box‐1‐inducible melanoma inhibitory activity is associated with nodal metastasis and lymphangiogenesis in oral squamous cell carcinoma

Abstract: Melanoma inhibitory activity (MIA) is an 11-kDa secretory protein isolated from malignant melanoma cells that is correlated with invasion and metastasis in various human malignancies. We examined MIA expression in 62 oral squamous cell carcinomas (OSCC) by immunohistochemistry. MIA expression was significantly associated with nodal metastasis (P = 0.00018). MIA expression was also associated with expression of high mobility group box-1 (HMGB1) (P < 0.0001) and lymph vessel density (P < 0.0001). Expression leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
99
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(107 citation statements)
references
References 46 publications
7
99
0
1
Order By: Relevance
“…[8][9][10] Recently, accumulating data suggested that HMGB1 expression was correlated with tumor development. [10][11][12][13] Upregulated expression of HMGB1 has been found in many tumor types including lung cancer. 3 However, high-mobility group box 1 (hMGB1) has been implicated in a variety of biologically important processes, including transcription, DNa repair, differentiation, development and extracellular signaling.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Recently, accumulating data suggested that HMGB1 expression was correlated with tumor development. [10][11][12][13] Upregulated expression of HMGB1 has been found in many tumor types including lung cancer. 3 However, high-mobility group box 1 (hMGB1) has been implicated in a variety of biologically important processes, including transcription, DNa repair, differentiation, development and extracellular signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Da HMGB1 auch die Neubildung von Lymphgef ä ß en f ö rdert, k ö nnte es auch zur lymphogenen Metastasierung beitragen. So wurde beim oralen Plattenepithelkarzinom eine Korrelation der HMGB1-Werte mit der Dichte der Lymphgef ä ß e und dem Lymphknoten-Status festgestellt [108] .…”
Section: Unempfindlichkeit Gegen ü Ber Wachstumsinhibitorenunclassified
“…Taguchi et al found that blockade of HMGB-RAGE signaling suppressed tumor growth as a result of decreased cell migration and invasiveness rather than proliferation or apoptosis (Taguchi et al, 2000). HMGB1 alone or by interaction with NF-kBp65 has been shown to bind specific region of melanocyte inhibitory activity (MIA) promoter in melanocytes and increase the expression of MIA protein, which enhances migration and invasion of tumor cells (Poser et al, 2003;Sasahira et al, 2008). HMGB1 was isolated using heparin-sepharose chromatography (Rauvala & Pihlaskari, 1987) and later was identified to contain a heparin-binding sequence in its amino terminus, suggesting its affinity for heparin (Cardin & Weintraub, 1989).…”
Section: Odsh Has Anti-metastatic and Anti-inflammatory Activities Inmentioning
confidence: 99%